Urgent Care Costs of Uncontrolled Asthma in Canada, 2004 - Soo Jin Seung; Nicole Mittmann (Canadian Respiratory Journal)
It has been more than a decade since Krahn evaluated the direct and indirect costs of asthma in Canada. Asthma is often uncontrolled and the cost of providing urgent care has not been determined. Hospitalizations, unscheduled physician visits, emergency department visits, drug treatments and ambulance rides are resources used by the uncontrolled asthmatic population, resulting in $162 million in costs annually. Improved control of asthma could decrease these costs.